Two developmental switches in GABAergic signalling: the K(+)–Cl(−) cotransporter KCC2 and carbonic anhydrase CAVII - Rivera, Claudio (Blackwell Science Inc, 2005)
GABAergic signalling has the unique property of ‘ionic plasticity’, which is based on short-term and long-term changes in the Cl(−) and HCO(3)(−) ion concentrations in the postsynaptic neurones. While short-term ionic plasticity is caused by activity-dependent, channel-mediated anion shifts, long-term ionic plasticity depends on changes in the expression patterns and kinetic regulation of molecules involved in anion homeostasis. During development the efficacy and also the qualitative nature (depolarization/excitation versus hyperpolarization/inhibition) of GABAergic transmission is influenced by the neuronal expression of two key molecules: the chloride-extruding K(+)–Cl(−) cotransporter KCC2, and the cytosolic carbonic anhydrase (CA) isoform CAVII. In rat hippocampal pyramidal neurones, a steep up-regulation of KCC2 accounts for the ‘developmental switch’, which converts depolarizing and excitatory GABA responses of immature neurones to classical hyperpolarizing inhibition by the end of the second postnatal week. The immature hippocampus generates large-scale network activity, which is abolished in parallel by the up-regulation of KCC2 and the consequent increase in the efficacy of neuronal Cl(−) extrusion. At around postnatal day 12 (P12), an abrupt, steep increase in intrapyramidal CAVII expression takes place, promoting excitatory responses evoked by intense GABAergic activity. This is largely caused by a GABAergic potassium transient resulting in spatially widespread neuronal depolarization and synchronous spike discharges. These facts point to CAVII as a putative target of CA inhibitors that are used as antiepileptic drugs. KCC2 expression in adult rat neurones is down-regulated following epileptiform activity and/or neuronal damage by BDNF/TrkB signalling. The lifetime of membrane-associated KCC2 is very short, in the range of tens of minutes, which makes KCC2 ideally suited for mediating GABAergic ionic plasticity. In addition, factors influencing the trafficking and kinetic modulation of KCC2 as well as activation/deactivation of CAVII are obvious candidates in the ionic modulation of GABAergic responses. The down-regulation of KCC2 under pathophysiological conditions (epilepsy, damage) in mature neurones seems to reflect a ‘recapitulation’ of early developmental mechanisms, which may be a prerequisite for the re-establishment of connectivity in damaged brain tissue.